The Algorithm of Digital Branding of Presidential Candidacy on Instagram: Duty of Computer Technology - Wibisono, Irawan (Postgraduate, University of Mataram, 2023)
The purpose of this study is to examine political branding in the campaign communication of presidential candidates Anies Baswedan and Muhaimin Iskandar on Instagram social media. Through the analysis of political branding theory and political communication, the researcher focuses on the dimensions of the campaign of presidential and vice presidential candidates Anies Baswedan and Muhaimin Iskandar through their Instagram social media, the results of this study are First, communication is the most crucial thing in political campaigns, especially general elections. Second, social media, especially Instagram, is a medium for Anies and Muhaimin to communicate programmes, clarify, respond to issues and campaign for their programmes. It allows for a two-way flow of information where there is interaction between Anies-Muhaimin and voters in social media posts. Images, videos and collaboration features support the packaging and dissemination of messages to voters. Third, both Anies and Muhaimin have the role of covering each other where Anies tries to display formal communication with coalition parties, Muhaimin displays his campaign through pilgrimage, friendship to kyai-kyai and Islamic boarding schools and participation with student movements affiliated with NU as the main basis for Muhimin's political branding